Severe acute respiratory syndrome coronavirus 2 vaccination for patients with solid cancer: Review and point of view of a French oncology intergroup (GCO, TNCD, UNICANCER). (June 2021) - Tougeron, David; Hentzien, Maxime; Seitz-Polski, Barbara; Bani-Sadr, Firouze; Bourhis, Jean; Ducreux, Michel; Gaujoux, Sébastien; Gorphe, Philippe; Guiu, Boris; Hoang-Xuan, Khê; Huguet, Florence; Lecomte, Thierry; et al.
Abstract: The impacts of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic on cancer care are multiple, entailing a high risk of death from coronavirus disease 2019 (COVID-19) in patients with cancer treated by chemotherapy. SARS-CoV-2 vaccines represent an opportunity to decrease the rate of severe COVID-19 cases in patients with cancer and also to restore normal cancer care. Patients with cancer to be targeted for vaccination are difficult to define owing to the limited contribution of these patients in the phase III trials testing the different vaccines. It seems appropriate to vaccinate not only patients with cancer with ongoing treatment or with a treatment having been completed less than 3 years ago but also household and close contacts. High-risk patients with cancer who are candidates for priority access to vaccination are those treated by chemotherapy. The very high-priority population includes patients with curative treatment and palliative first- or second-line chemotherapy, as well as patients requiring surgery or radiotherapy involving a large volume of lung, lymph node and/or haematopoietic tissue. When possible, vaccination should be carried out before cancer treatment begins. SARS-CoV-2 vaccination can be performed during chemotherapy while avoiding periods of neutropenia and lymphopenia. For organisational reasons, vaccination should be performed in cancer care centres with messenger RNA vaccines (or non-replicating adenoviral vaccines in non-immunocompromised patients). Considering the current state of knowledge, the benefit-risk ratio strongly favours SARS-CoV-2 vaccination of all patients with cancer. To obtain more data concerning the safety and effectiveness of vaccines, it is necessary to implement cohorts of vaccinated patients with cancer. Highlights: Ultrapriority for severe acute respiratory syndrome coronavirus 2 vaccination is for patients with curative intent treatment. Priority is for patients with cancer treated with chemotherapy. Vaccination can be carried out during chemotherapy avoiding periods of bone marrow aplasia. Contraindications to vaccines if there is an history of allergy to vaccine components.